1992
DOI: 10.1038/bjc.1992.366
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated hypoglycaemia in a murine cachexia model

Abstract: SummaryAnimals bearing a cachexia-inducing tumour, the MAC16 adenocarcinoma, showed a progressive decrease in blood glucose levels with increasing weight loss, while animals bearing a histologically similar tumour, the MAC13 adenocarcinoma, showed no change in either body weight or blood glucose levels with growth of the tumour. The effect of the MAC16 tumour on blood glucose levels appeared to be unrelated to food intake, glucose consumption by the tumour, or to the production of increased levels of IGF-I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This suggests that the two substances are identical. Intravenous injection of this substance in mice causes a state of cachexia similar to that observed after administration of the murine material (Todorov et al, 1996a) in mice bearing the MAC16 tumour in that (a) weight loss occurs without a reduction in food and water intake (Beck and Tisdale, 1987) and thus is not due to toxicity of the material, (b) weight loss can be attenuated by prior administration of the monoclonal antibody, (c) there is marked hypoglycaemia (McDevitt and Tisdale, 1992) and (d) there is a decreased level of plasma triglycerides; in the last respect the effect is unlike that of TNF-a, which causes an increase (Mahony et al, 1988). This observation, together with the finding of decreased plasma levels of 3-hydroxybutyrate, suggests that energy expenditure may be increased.…”
Section: Discussionmentioning
confidence: 79%
“…This suggests that the two substances are identical. Intravenous injection of this substance in mice causes a state of cachexia similar to that observed after administration of the murine material (Todorov et al, 1996a) in mice bearing the MAC16 tumour in that (a) weight loss occurs without a reduction in food and water intake (Beck and Tisdale, 1987) and thus is not due to toxicity of the material, (b) weight loss can be attenuated by prior administration of the monoclonal antibody, (c) there is marked hypoglycaemia (McDevitt and Tisdale, 1992) and (d) there is a decreased level of plasma triglycerides; in the last respect the effect is unlike that of TNF-a, which causes an increase (Mahony et al, 1988). This observation, together with the finding of decreased plasma levels of 3-hydroxybutyrate, suggests that energy expenditure may be increased.…”
Section: Discussionmentioning
confidence: 79%
“…Hypoglycaemia has previously been reported with both human (Nolop et al, 1987) and experimental tumours such as the MAC16 adenocarcinoma (McDevitt and Tisdale, 1992) and appears to be unrelated to food intake, glucose consumption by the tumour or insulin-like growth factors (either IFG-I or IGF-II) produced by tumours. Insulin levels have been found to be low in cases of tumour-associated hypoglycaemia (Bibby et al, 1987) and the production of an insulin-like factor by the tumour was suggested as the cause of the enhanced peripheral glucose uptake.…”
Section: mentioning
confidence: 99%
“…Many of the effects of LMF in mice are similar to those produced by the MAC16 tumour. Thus both produce hypoglycaemia (McDevitt and Tisdale, 1992), lipid depletion (Beck and Tisdale, 1987) and an increased 14 CO 2 production from […”
Section: Discussionmentioning
confidence: 99%
“…Despite fat mobilisation there was a decrease in blood glucose levels. Hypoglycaemia occurs in mice bearing a cachexia-inducing tumour (MAC16), although the mechanism by which this occurs is not known (McDevitt and Tisdale, 1992).The purpose of the present study was to investigate the effect of LMF on glucose and lipid metabolism in vivo in order to quantitate the effect on energy utilisation. …”
mentioning
confidence: 99%
See 1 more Smart Citation